BIOACTIVE CONSTITUENTS FROM THE LEAVES OF MELASTOMA MALABATHRICUM L. - Deni Susanti; Hasnah M. Sirat; Farediah Ahmad; Rasadah Mat Ali (Jurnal Ilmiah Farmasi, 2008)
ABSTRACTPhytochemical and bioactivity studies of the leaves of Melastoma malabathricum L.(Melastomataceae) have been investigated. The n-hexane extract yielded -amyrin, patriscabatrineand auranamide, ethyl acetate extract gave quercetin and quercitrin, and methanol extract gavequercitrin and kaempferol-3-O-(2”,6”-di-O-p-trans-coumaroyl)glucoside. The crude extracts andisolated compounds were screened for their antioxidant and cytotoxic activities. The antioxidantassay was carried out by FTC and DPPH radical scavenging method. Kaempferol-3-O-(2”,6”-di-Op-trans-coumaroyl)-glucoside, quercetin and quercitrin showed strong activities with inhibition morethan 90% in the FTC method. Quercetin was found to be the most active as radical scavenger inDPPH method with IC50 of 0.69 M. -Amyrin and kaempferol-3-O-(2”,6”-di-O-p-transcoumaroyl)glucoside demonstrated the strongest activities in the anti-inflammatory assay of TPAmouse ear oedema with IC50 of 0.11 and 0.34 mM/ear, respectively.Keywords: Antiinflammatory, Antioxidant, Flavonoids, Melastomataceae, Melastomamalabathricum, Terpenoid